Avaliação de métodos de coleta, centrifugação e manejo pré-coleta de fezes em estudos de digestibilidade para o tambaqui - Assis, Rudney Weiber Silva de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The study aimed to obtain information on methods of collection and processing of feces to prepare a protocol on protein and energy digestibility studies for tambaqui with average weight of 230,74g, by determining the best food pre-collection of stool frequency; assessing the effect of spin tambaqui feces and determining the best time to collect feces. The test of adequacy of food frequency was divided into daytime phase (fishes fed with different frequencies: 08:00 and 18:00, 8:00, 13:00 and 18:00, 08:00, 11:20, 14:40 and 18:00) and night phase (20:00 and 06:00, 20:00, 01:00 and 06:00, 20:00, 23:20, 02:40 and 06:00). In both cases (daytime and nighttime), the feces were collected every two hours. The evaluation parameter used to determine the best feed rate was the amount of stool in the dry matter. The testo f the effect of centrifugation was performed by determining the best for determining the best time and feces spin speed was lined with nine treatments following a factorial 3 X 3 comprises three rotation speeds (3000, 4500 and 6000 RPM) and three centrifugation time of stool (10, 20, and 30'), plus two treatments witnesses: feces collection by decantation without centrifuging and collecting stool by dissecting the final region of the digestive tract. The evaluation parameter used to determine the best response was the concentration of the marker protein and energy as well as its digestibility. For testing stool collection intervals were considered five treatments: 1h; 2h; 4h; 8h and 12h, with three replications. The best answer evaluation parameter was the concentration of protein and energy in the stool, and also their digestibility. It was concluded that there was no effect of different feeding frequencies on the volume of dry matter of feces, possibly tambaqui's ability to store food for a relatively long time. In general, no greater accuracy in collecting stool with centrifugation, and may be observed loss coefficients ...

O estudo teve como objetivo obter informações sobre métodos de coleta e processamento de fezes para elaboração de um protocolo em estudos de digestibilidade de proteína e energia para o tambaqui com peso médio de 230,74g, através da determinação da melhor frequência alimentar pré-coleta de fezes; da avaliação do efeito da centrifugação de fezes do tambaqui e da determinação do melhor tempo de coleta de fezes. O ensaio sobre adequação da frequência alimentar foi dividido em fase diurna (peixes alimentados com diferentes frequências: 08:00 e 18:00; 8:00, 13:00 e 18:00; 08:00, 11:20, 14:40 e 18:00) e fase noturna (20:00 e 06:00; 20:00, 01:00 e 06:00; 20:00, 23:20, 02:40 e 06:00). Nos dois casos (período diurno e noturno), as fezes foram coletadas a cada duas horas. O parâmetro de avaliação utilizado para determinação da melhor frequência alimentar foi o volume de fezes na matéria seca. O ensaio do efeito da centrifugação foi realizado por meio da determinação dos melhores tempos e rotações de centrifugação das fezes em um delineamento com nove tratamentos seguindo um esquema fatorial 3 X 3 constituído por três velocidades de rotação (3000, 4500 e 6000 RPM) e três tempo de centrifugação (10, 20 e 30'), acrescidos de dois tratamentos testemunhas: coleta de fezes por decantação sem centrifugação e coleta de fezes por dissecação da região final do trato digestório. O parâmetro de avaliação utilizado para determinação da melhor resposta foi a concentração do marcador, da proteína e da energia como também dos seus coeficientes de digestibilidade. Para o ensaio de intervalos de coleta de fezes foram considerados cinco tratamentos: 1h; 2h; 4h; 8h e 12h, com três repetições. O parâmetro de avaliação da melhor resposta foi a concentração da proteína e energia nas fezes, e também os seus coeficientes de digestibilidade. Conclui-se que não houve efeito das diferentes frequências...
Keywords: Peixe; Tambaqui (Peixe); Dissecação; Peixe - Alimentação; Digestão; Fezes; Fishes